Regionalização da saúde materna e infantil no estado do Ceará: contando glórias ou contendo soluços? - Tajra, Fábio Solon (2016)
The health management for ensuring access has made the challenge of the construction of the Brazilian health system process. Over twenty-two years after the redefinition of the care model to be experienced and the implementation of the first teams of the Family Health Strategy, we can say that there was a change in this scenario. However, leverage this discussion incorporated the comprehensive care of thematic and interconnection services in networks. Some authors relate various aspects, be they perceived in a macro and / or micro-social context, relationships and attempts at integration, coordination and cooperation between the services, together with the role of individuals (managers, health professionals and users) before all organizational dynamics. The process of regionalization and implementation of the Care Network Maternal and Child Health (Stork Network) in the country sought to answer this demand. However, studies are needed to understand the best practices and points to be improved and refined over the political and administrative approach to be adopted. It is a qualitative approach to evaluative study aimed to evaluate the regionalization of maternal and child health in the state of Ceará from the experiences of users and professionals of maternal and child health services, as well as supporters of national policy, the central level managers and regional state of Ceará. We used theoretical framework related to issues of access, comprehensive care and interconnection of health services in networks from a hermeneutic perspective. Five units of meaning were prepared: to be pregnant; possible way of care; technical assistance and potential support to women's health and child care; access to health and pilgrimage; and, organization and operation of network services. In the quest for health care, difficulties women's needs were recognized and observed in access to health services. It is noticed a pilgrimage in search of maternal and child health services, coupled with problems of integration and coordination between services. Thus, it is necessary to invest in systemic-strategic rationales to do justice to the complexity of the above pointed theme. Points to the revision of strategies to ensure that women access to health actions and services in a comprehensive perspective, allow the articulation, integration and interconnection of services and, above all, value and respect their rights.